Mitochondrial transcription factor B2 is essential for mitochondrial and cellular function in pancreatic β-cells - Lisa M. Nicholas; Bérengère Valtat; Anya Medina; Lotta Andersson; Mia Abels; Inês G. Mollet; Deepak Jain; Lena Eliasson; Nils Wierup; Malin Fex; Hindrik Mulder (Elsevier, 2017)
Objective: Insulin release from pancreatic β-cells is controlled by plasma glucose levels via mitochondrial fuel metabolism. Therefore, insulin secretion is critically dependent on mitochondrial DNA (mtDNA) and the genes it encodes. Mitochondrial transcription factor B2 (TFB2M) controls transcription of mitochondrial-encoded genes. However, its precise role in mitochondrial metabolism in pancreatic β-cells and, consequently, in insulin secretion remains unknown. Methods: To elucidate the role of TFB2M in mitochondrial function and insulin secretion in vitro and in vivo, mice with a β-cell specific homozygous or heterozygous knockout of Tfb2m and rat clonal insulin-producing cells in which the gene was silenced were examined with an array of metabolic and functional assays. Results: There was an effect of gene dosage on Tfb2m expression and function. Loss of Tfb2m led to diabetes due to disrupted transcription of mitochondrial DNA (mtDNA) and reduced mtDNA content. The ensuing mitochondrial dysfunction activated compensatory mechanisms aiming to limit cellular dysfunction and damage of β-cells. These processes included the mitochondrial unfolded protein response, mitophagy, and autophagy. Ultimately, however, these cell-protective systems were overridden, leading to mitochondrial dysfunction and activation of mitochondrial-dependent apoptotic pathways. In this way, β-cell function and mass were reduced. Together, these perturbations resulted in impaired insulin secretion, progressive hyperglycemia, and, ultimately, development of diabetes. Conclusions: Loss of Tfb2m in pancreatic β-cells results in progressive mitochondrial dysfunction. Consequently, insulin secretion in response to metabolic stimuli is impaired and β-cell mass reduced. Our findings indicate that TFB2M plays an important functional role in pancreatic β-cells. Perturbations of its actions may lead to loss of functional β-cell mass, a hallmark of T2D.